Strategi Pemilihan Proyek Pembangunan Pembangkit Listrik dengan Metode Analytical Hierarchy Process (AHP) di PT Pembangkitan Jawa Bali (PT PJB) - Heru Budi Pratomo; Bambang Tjahjadi (Jurnal Bisnis dan Keuangan, 2019)
The government launched a 35,000 MW program based on the Decree of the Minister of Energy and Mineral Resources of the Republic of Indonesia especially for outside Java region as part of development of country infrastructure. To be able to continue to grow and compete, PT PJB as a company engaged in the field of electric power producers must have good investment plan, one of the investments that can be made is through participation in electric power plant development projects. The purpose of this study is to find out the influential criteria in making decisions and provide recommendations to PT PJB in the formulation of alternative priority scales for power plant development projects selection strategy. This study uses a qualitative approach with a case study approach. Samples from this study were key informants using purposive sampling and filling out questionnaires. The results of this study are the formation of 3 criteria which are the best priorities, namely generating new revenue with a weight of 0.177, market share with a weight of 0.134 and increasing opportunities in the future with a weight of 0.127. While the determination of the main alternative for the construction of the Power Plant Project is the Java 7 PLTU of 16.3%, the Java 8 PLTU of 12.9% and the Java 3 PLTGU of 10%.